Transactions identitaires des formateurs d’agents de prévention et de sécurité et enjeux de professionnalisation - Kananny Ag Hartata; Thérèse Perez-Roux (Éducation et Socialisation)
The text focuses on the construction of professional identity among trainers in private security, in a developing but still poorly structured sector. It concerns in both the identity transactions and the professionalization dynamics of these trainers, based on a study of representations, values and "declared" professional practices. The research data come from semi-structured interviews conducted with security trainers on two different sites (a vocational training center in private security and a vocational high school). The results highlight the importance of the career path in the approach taken by the trainer, and in relation to the practitioners in the field, and shed light on the type of relationships within a group of trainers and the trainees. These results help to understand the rapport with a training activity organized around shared values and perceptions of function, and this rapport appears to be more or less contrasted according to the different sectors. Finally, the study highlights issues of professional recognition identifiable at different levels.